Improving Fine Motor Skills Of Children Aged 5–6 Years Through Hand Puppet-Assisted Role-Play Activities: A Classroom Action Research Study - Ziana Abas; Rudy Juli Saputra; Rahma Rahma (Darul Ilmi Bina Insan Foundation, 2026)
Fine motor skills are essential for early childhood development because they support children's ability to perform activities requiring finger coordination, hand flexibility, and hand-eye coordination. Preliminary observations at UPTD TK Negeri Cut Meutia revealed that the fine motor skills of children aged 5–6 years had not yet reached the expected developmental level, with only 42% of children achieving the predetermined mastery criteria. Therefore, an effective learning strategy was needed to improve children's fine motor development. This study aimed to improve the fine motor skills of children aged 5–6 years through hand puppet-assisted role-play activities. The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of two cycles. The participants were 10 children in Group B at UPTD TK Negeri Cut Meutia. Data were collected through observation sheets, field notes, and documentation, and were analyzed descriptively using percentage calculations. The findings showed a significant improvement in children's fine motor skills throughout the research cycles. Learning mastery increased from 42% in the pre-cycle stage to 65% in Cycle I and reached 80% in Cycle II. Children demonstrated better finger coordination, improved hand flexibility, and greater participation in learning activities involving storytelling and role-play. The study concludes that hand puppet-assisted role-play activities effectively improve the fine motor skills of children aged 5–6 years. The use of hand puppet media provides meaningful and enjoyable learning experiences that support children's motor development and active engagement in classroom activities.